2x+73=8x-11

Simple and best practice solution for 2x+73=8x-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+73=8x-11 equation:


Simplifying
2x + 73 = 8x + -11

Reorder the terms:
73 + 2x = 8x + -11

Reorder the terms:
73 + 2x = -11 + 8x

Solving
73 + 2x = -11 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
73 + 2x + -8x = -11 + 8x + -8x

Combine like terms: 2x + -8x = -6x
73 + -6x = -11 + 8x + -8x

Combine like terms: 8x + -8x = 0
73 + -6x = -11 + 0
73 + -6x = -11

Add '-73' to each side of the equation.
73 + -73 + -6x = -11 + -73

Combine like terms: 73 + -73 = 0
0 + -6x = -11 + -73
-6x = -11 + -73

Combine like terms: -11 + -73 = -84
-6x = -84

Divide each side by '-6'.
x = 14

Simplifying
x = 14

See similar equations:

| -18=2a | | 6m^2+9m-6=0 | | 13x-6=9x+14 | | 3x+10+40= | | 10x/y | | -3(-7+m)= | | 3x-5=137 | | 17x=5y+1 | | -4a^2-45a-50=0 | | x+48=x | | 8v+13=3v+18 | | 3x+40+10=180 | | 6(2x+4)=3(8+4x) | | x^-3/2=0 | | 6x-5y+3=-27 | | 9cot^2x+1=4 | | X^3-4x^2-14x-60=0 | | 3x+10+40=360 | | 9=3p+6 | | 8b-13b= | | 9cot^2x=4 | | x+4+2x=137 | | 11s+12t=93 | | P=275/12i1714 | | 7w+4=5w-10 | | 6(2Y+2)-9=3 | | 1-7x=6x-129 | | 2(T-2)+9=-9 | | 5(3x-1)=-10x+20 | | 6/(2/3) | | 9(5n+4)= | | 5p+6q=54 |

Equations solver categories